Is congestion pricing fair? Consumer and citizen perspectives on equity effects - Jonas Eliasson (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This paper discusses and analyses whether congestion charges can be considered to be "fair" in different senses to the word. Two different perspectives are distinguished: the consumer perspective and the citizen perspective. The consumer perspective is the traditional one in equity analyses, and includes changes in travel costs, travel times and so on. Using data from four European cities, the analysis shows that high-income groups pay more than low-income groups, but low-income groups pay a higher share of their income. This paper argues that which distributional measure is most appropriate depends on the purpose(s) of the charging system. The citizen perspective is about individuals' view of social issues such as equity, procedural fairness and environmental issues. This paper argues that an individual can be viewed as a "winner" from a citizen perspective if a reform (such as congestion pricing) is aligned with her views of what is socially desirable. Using the same data set, this paper analyses to what extent different income groups "win" or "lose" from a citizen perspective - i.e., to what extent congestion pricing is aligned with the societal preferences of high- and low-income groups.
Keywords: 330; City-Maut; Gerechtigkeit; Stockholm; Göteborg; Helsinki; Lyon; Finnland; Frankreich; Schweden